ANALISIS DETEKSI ANOMALI DIGIT LAPORAN KEUANGAN MENGGUNAKAN HUKUM BENFORD - Trixie Ivena Susanto; Carmel Meiden; Dergibson Siagian (Bajang Institute, 2026)
This study aims to examine the conformity of first-digit and second-digit distributions in financial statements of financial sector companies listed on the Indonesia Stock Exchange during the period 2021–2024 using Benford’s Law. This research employs a quantitative descriptive approach using secondary data obtained from annual financial reports. The analysis focuses on evaluating the distribution of digits and measuring deviations using Chi-Square (χ²) as the primary statistical test and Mean Absolute Deviation (MAD) as a supporting indicator. The results indicate that most companies generally conform to Benford’s Law; however, several issuers exhibit significant deviations. The Chi-Square test shows that seven companies deviate in first-digit analysis and five companies in second-digit analysis. In addition, MAD results reveal that a considerable number of companies fall into marginal and nonconformity categories, indicating potential numerical irregularities. These findings suggest that Benford’s Law can be used as an effective screening tool to identify early indications of unusual numerical patterns in financial statements.